Bibliografijos ir kritikos žurnalas „Knygos“ - Basiulis, Jonas (Knygotyra, 1972)
The journal “Knygos” was the source of the current enumerative, critical and partly retrospective bibliography. In addition, it contained the bibliography of Lituanistics and periodicals, the published articles on bibliography and booklore, chronicle notes from the library life, etc. The journal had a vast program and was expected to appear six times a year. Due to the bourgeois government’s disregard of culture problems and shortage of means the planned program was not fulfilled. In 1922 two journal issues appeared: the first and the second-the double one (No 2/3); in 1924 the third-the threefold issue (No 4/6) came out and after that the publication ceased. On the basis of archival material the paper reviews the history of the journal, its edition and distribution, the contents, methodical problems and bibliographing of printed publications. In 1924 the character of the journal completely changed and it became only the source of retrospective bibliography. The edition was appearing irregularly and contained the bibliography of Lithuanian books and periodicals from their origin until 1911. The journal “Knygos” is a valuable source of bibliography of that time. Besides, its appearance gave rise to the current national bibliography. Therefore, the journal is of interest to those who study the history and technique of recording the enumerative bibliography in Lithuania. The history of the journal publication also shows the indifference of the ruling circles to the problerns of national bibliography.